Viral agents as biological weapons and agents of bioterrorism - Bronze, Michael S; Huycke, Mark M; Machado, Linda J; Voskuhl, Gene W; Greenfield, Ronald A (The American journal of the medical sciences, 2002)
Multiple viral agents have been classified by the CDC as potential weapons of mass destruction or agents for biologic terrorism. Agents such as smallpox, viral hemorrhagic fever viruses, agents of viral encephalitis, and others are of concern because they are highly infectious and relatively easy to produce. Although dispersion might be difficult, the risk is magnified by the fact that large populations are susceptible to these agents and only limited treatment and vaccination strategies exist. Although the risk of large-scale bioterrorism using viral agents is small, public health programs and health care providers must be prepared for this potentially devastating impact on public health.